Bandwidth Reconfigurable Metamaterial Arrays - Nathanael J. Smith; Dimitris Papantonis; John L. Volakis (International Journal of Antennas and Propagation)
Metamaterial structures provide innovative ways to manipulate electromagnetic wave responses to realize new applications. This paper presents a conformal wideband metamaterial array that achieves as much as 10 : 1 continuous bandwidth. This was done by using interelement coupling to concurrently achieve significant wave slow-down and cancel the inductance stemming from the ground plane. The corresponding equivalent circuit of the resulting array is the same as that of classic metamaterial structures. In this paper, we present a wideband Marchand-type balun with validation measurements demonstrating the metamaterial (MTM) array’s bandwidth from 280 MHz to 2800 MHz. Bandwidth reconfiguration of this class of array is then demonstrated achieving a variety of band-pass or band-rejection responses within its original bandwidth. In contrast with previous bandwidth and frequency response reconfigurations, our approach does not change the aperture’s or ground plane’s geometry, nor does it introduce external filtering structures. Instead, the new responses are realized by making simple circuit changes into the balanced feed integrated with the wideband MTM array. A variety of circuit changes can be employed using MEMS switches or variable lumped loads within the feed and 5 example band-pass and band-rejection responses are presented. These demonstrate the potential of the MTM array’s reconfiguration to address a variety of responses.